Interview with Nibedita Nag, one of the founders of the communist movement of Dhaka in the 1940s, wife of Nepal Nag. Interviewed in Dhaka, 07/03/2000 - Kabir, Shahriar.
Interview with Nibedita Nag, one of the founders of the communist movement of Dhaka in the 1940s, wife of Nepal Nag. Interviewed in Dhaka, 07/03/2000.